Strength training for endurance runners with applications to other events - Christensen, S.
About strength training for endurance runners: periodization, sessions, drills. SUMMARY: Quite often the scope of strength training is viewed as building "big muscles," since size is associated with strength. Although this is valid for football and the throwing events in track and field, it is not the training objective of endurance runners. The scope of strength training for distance runners is to make the neuromuscular system function as effectively as possible in order to meet the physiological needs of the runner. Therefore, strength training is undertaken to develop power or the ability of the muscles to apply force at the proper rate. Consequently, the role of this strength training is to create a physiological foundation in order to improve one's overall ability to meet the needs of distance running and enhance performance. Such an approach is the most important ingredient in the "making of a champion."